SYNTHESIS AND STABILITY OF RESVERATROL-CONJUGATED GOLD NANOPARTICLES MODIFIED WITH POLYETHYLENE GLYCOL - ISWANDANA, RADITYA; NURSELVIANA, RICHA; SUTRIYO, SUTRIYO (International Journal of Applied Pharmaceutics, 2020)
Objective: Gold nanoparticles (AuNPs) are highly useful for drug delivery, but their application is limited by their stability as they readily aggregate. This issue can be prevented by adding a stabilizing agent such as resveratrol (RSV), which is a polyphenol derived from plants, that is used to prevent cancer. Therefore, we propose a novel method to prepare stable RSV-conjugated nanoparticles modified with polyethylene glycol (RSV-AuNP-PEG). Methods: In the first step, the Turkevich method was used to synthesize the AuNPs. Then, PEG was added as stabilizer agent and conjugated with RSV. The synthesized conjugates were characterized using ultraviolet-visible spectrophotometry, Fourier transform infrared spectroscopy, particle size analysis, and high-performance liquid chromatography. Results: The obtained RSV-AuNP-PEG had a particle size of 83.93 nm with a polydispersity index (PDI) of 0.562 and formed a translucent purple-red fluid in solution. The zeta potential was −22.9 mV, and the highest entrapment efficiency was 75.86±0.66%. For comparison, the RSV-AuNP solution was purple and turbid, the particle size was 51.97 nm with a PDI of 0.694, and the zeta potential was −24.6 mV. The stability test results showed that the storage stability of RSV-AuNP-PEG was better than that of AuNP-RSV. Further, the RSV-AuNP-PEG was shown to be most stable in 2% bovine serum albumin (BSA) while the AuNP-RSV was most stable in 2% BSA in phosphate-buffered saline pH 7.4. Conclusion: These results show that modification of RSV-conjugated AuNPs with PEG effectively prevents their aggregation in storage, but only in certain mediums.